ANALYSIS OF NARRATIVE MATHEMATICAL QUESTIONS ON TEXTBOOKS BASED ON SOLO TAXONOMY AND MATHEMATICAL POWER - Kusmaryono, Imam (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2017)
This study aimed to identify the proportion of diversity and suitability of narrative mathematical questions with SOLO taxonomy level and mathematical power ability. The research was conducted through quantitative descriptive. Sources of data in the forms of narrations contained in mathematics textbooks. The research procedure was conducted by making the classification and determining the percentage of the narrations based on the compatibility of SOLO taxonomy and the mathematical power ability. The results showed that, the narrative mathematical questions with uni-structural level are of 7.5%, multi-structural of 33.8%, relational of 46.6% and extended abstract of 12.1 %. In terms of compatibility of the narrativeÂ  questions were able to measure 23% reasoning aspect, 18% problem solving, 8.3% connection, 28% communication and 22.6% mathematical representation. In general, mathematics textbooks as the object of research should be revised, since they have not yet achieved the ideal alignment between SOLO taxonomy based on grade level and the objective of learning develop mathematical power